Foundations of mathematics - Logic at Harvard : Essays in Honor of Hugh Woodin's 60th Birthday (Cambridge, MA 27-29 March, 2015); Caicedo, Andres Eduardo; Cummings, James; Koellner, Peter; Larson, Paul B. (Providence : American Mathematical Society, 2017)
Contains the proceedings of the Logic at Harvard conference in honour of W. Hugh Woodin's 60th birthday. The topics cover many of the areas central to Woodin's work, including large cardinals, determinacy, descriptive set theory and the continuum problem, as well as connections between set theory and Banach spaces, recursion theory, and philosophy, each reflecting a period of Woodin's career.
H. G. Dales, Norming infinitesimals of large fieldsT. A. Slaman and M. I. Soskova, The enumeration degrees: Local and global structural interactionsA. S. Kechris, M. Sokic, and S. Todorcevic, Ramsey properties of finite measure algebras and topological dynamics of the group of measure preserving automorphisms: Some results and an open problemA. E. Caicedo and J. Hilton, Topological Ramsey numbers and countable ordinalsV. Gitman and J. D. Hamkins, Open determinacy for class gamesM. Malliaris and S. Shelah, Open problems on ultrafilters and some connections to the continuumP. D. Welch, Obtaining Woodin's cardinalsR. Schindler, Woodin's axiom (*), or Martin's maximum, or both?G. Sargsyan, Translation procedures in descriptive inner model theoryS. Cramer, Implications of very large cardinalsJ. T. Moore, What makes the continuum $\aleph_2$P. Maddy, Set-theoretic foundations.
Includes bibliographical references.
Keywords: Set theory -- Congress; Continuum hypothesis -- Congress